‘‘The effectiveness of Social Dialogue in addressing the economic problems in Zimbabwe” (January 2008-December 2014) - Bikoloni, Brave (2017)
The environment within which social dialogue operates is shaped by a number of factors, most of which are economic, social, political, environmental and legal. The economic, social and political developments in Zimbabwe from 2008, and 2014 posed various challenges to the economy of the country. In an attempt to find solutions to the challenges affecting the country, policy makers pursued various avenues, including social dialogue. Against this background, it was of interest to ascertain the effectiveness of social dialogue as a strategy in addressing the economic challenges in Zimbabwe from January 2008 to December 2014. The researcher was mostly interested in investigating how the social dialogue process was undertaken at the national level and the problems that were faced by the respective constituents. In undertaking the study, conducted were face to face interviews with respondents in order to gain more insight through probing. Arising out of the study, it emerged that social dialogue had indeed been used as a strategy to help in addressing the economic problems in the country, albeit without much success. The findings of the study points to the fact that; while social dialogue was pursued, it was not effective as envisaged owing to the voluntary nature and lack of a legislative framework to govern the process.Going forward, the study has brought to the fore, the importance of legislation on the state-run social dialogue process, as in form of strengthening the Tripartite Negotiating Forum (TNF) secretariat in order for it to be better capacitated to execute its mandate. In terms of the economy, the findings point to a great need to depoliticise public policies to better function.